Filtration performance and modeling of granular bed for dust removal from coal pyrolytic vapors - Yang, Shuaiqiang; Du, Lin; Ding, Guangchao; Liu, Runguo; Song, Wenli; Li, Songgeng (Chinese journal of chemical engineering, 2024)
[Display omitted] •A granular bed was designed and integrated into a 10 t·d–1 coal pyrolysis facility.•A model is established to describe the granular bed performance.•The effluent dust size after filtration appears a bimodal distribution.•The effect of filtration bed on pyrolytic products has been discussed. Dust removal from pyrolytic vapors at high temperatures is an obstacle to the industrialization of the coal pyrolysis process. In this work, a granular bed with expanded perlites as filtration media was designed and integrated into a 10 t·d–1 coal pyrolysis facility. The testing results showed that around 97.56% dust collection efficiency was achieved. As a result, dust content in tar was significantly lowered. The pressure drop of the granular bed maintained in the range of 356 Pa to 489 Pa. The dust size in the effluent after filtration exhibited a bimodal distribution, which was attributed to the heterogeneity of the dust components. The effects of filtration bed on pyrolytic product yields were also discussed. A modified filtration model based on the macroscopic phenomenological theory was proposed to describe the performance of the granular bed. The computation results were well agreed with the experimental data.